Acute Insulin Resistance and Rapid Alterations in Neuronal Derived Blood Exosome Concentration After Branched Endovascular Aortic Aneurysm Repair. (March 2020) - Hiramoto, Jade S.; Elahi, Fanny M.; Gasper, Warren J.; Reilly, Linda M.; Chuter, Timothy A.; Goetzl, Edward J.
Abstract : Objective: Hyperglycaemia following branched endovascular repair (BEVAR) of extensive aortic aneurysms is associated with post-operative lower extremity weakness (LEW). Insulin administration to maintain euglycaemia appears to decrease LEW rates. The purpose of this study was to examine changes in insulin receptor content of neuron derived blood exosomes (NDEs) after BEVAR. Methods: Ten patients with a range of post-operative lower extremity neurological deficits after elective BEVAR were included in the study. Blood samples were collected pre-operatively, immediately after aneurysm repair, and on post-operative day 1. NDE insulin receptor substrate proteins were quantified by enzymevlinked immunosorbent assays. Results: NDE levels of phosopho-serine312-type 1 insulin receptor substrate ([P-Ser312-IRS1], an inhibitor of insulin signalling) increased sevenfold in the immediate post-operative period (from 7.90 ± 0.89 to 58.54 ± 6.77 pg/mL; p < .001), whereas those of pan-tyrosine-phospho insulin receptor substrate ([P-panTyr-IRS1], which facilitates insulin signalling), rose only 50% (from 0.41 ± 0.07 to 0.63 ± 0.10 pg/mL; p = .03). As a result, the mean ratio of P-Ser312-IRS1 to P-panTyr-IRS1, which reflects the level of insulin resistance, increased fivefold immediately post-operatively (from 22.31 ± 3.28 to 106.33 ± 11.83; p < .001) and returned to normal levels by the next day (18.72 ± 1.87). Conclusion: BEVAR is associated with an acute state of insulin resistance within neuronal tissue. Further studies in a larger cohort of patients are needed to understand the potential interconnected processes of insulin resistance, hyperglycaemia, and spinal cord ischaemia after extensive endovascular aortic procedures.